Elite sport - return to cross border competition guidance (2020)
The following guidance covers Stage Four of the proposed five stage framework for returning to full unrestricted elite sporting Competition and has been produced by a working group of leading sports Chief Medical Officers and partner organisation representatives across Olympic, Paralympic and professional sports on behalf of the Department for Digital, Culture, Media & Sport (DCMS).